Analisis Strategi dan Perkembangan Industri di Indonesia - Amelia Endang Puput Lestari; Aulina Nur Fadilah; Sulis Setiawati; Enrico Valentino Riyadi; Naerul Edwin Kiky Aprianto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study analyzes the strategy and development of industry in Indonesia with the aim of identifying the main factors that influence the growth of the industrial sector. This study uses a qualitative method with a literature study through related documents and journals. The results of the study indicate that industrial growth is influenced by economic, social, technological factors, and government policies. These factors include the growth of the manufacturing sector, the availability of skilled labor, investment, and the adoption of Industrial Revolution 4.0 technology. Government strategies such as Making Indonesia 4.0, tax incentives, and infrastructure improvements have played a significant role in encouraging industrial competitiveness in the global market. However, challenges such as limited infrastructure, high production costs that hinder growth, especially for Micro, Small and Medium Enterprises (MSMEs) and product quality that does not meet international standards are still major obstacles. This study concludes that in order to maintain competitiveness, industry must increase innovation, implement new technologies and strengthen the quality of human resources. The active involvement of the government in supporting policies and infrastructure is crucial to encourage sustainable industrial development.